2020
DOI: 10.3390/reactions1020013
|View full text |Cite
|
Sign up to set email alerts
|

Smart Designs of Anti-Coking and Anti-Sintering Ni-Based Catalysts for Dry Reforming of Methane: A Recent Review

Abstract: Dry reforming of methane (DRM) reaction has drawn much interest due to the reduction of greenhouse gases and production of syngas. Coking and sintering have hindered the large-scale operations of Ni-based catalysts in DRM reactions at high temperatures. Smart designs of Ni-based catalysts are comprehensively summarized in fourth aspects: surface regulation, oxygen defects, interfacial engineering, and structural optimization. In each part, details of the designs and anti-deactivation mechanisms are elucidated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 194 publications
(257 reference statements)
0
23
0
Order By: Relevance
“…6−8 One significant deactivation mechanism for DRM catalysts is the sintering of the active metal sites, a high-temperature process by which the catalytically active metal atoms migrate (Ostwald ripening) 9,10 and/or metal particles coalesce and form less and/or fewer active sites for the reaction (sintering). 11,12 Our research groups have previously reported that the initial deactivation of Ni/Al 2 O 3 catalysts under DRM conditions is caused by the sintering of the Ni particles with an apparent activation energy of 161 kJ mol −1 . 13 In order to overcome catalyst deactivation due to sintering, overcoating the catalyst with a metal oxide layer by atomic layer deposition (ALD) has been shown to be an effective catalyst stabilization strategy.…”
Section: Introductionmentioning
confidence: 99%
“…6−8 One significant deactivation mechanism for DRM catalysts is the sintering of the active metal sites, a high-temperature process by which the catalytically active metal atoms migrate (Ostwald ripening) 9,10 and/or metal particles coalesce and form less and/or fewer active sites for the reaction (sintering). 11,12 Our research groups have previously reported that the initial deactivation of Ni/Al 2 O 3 catalysts under DRM conditions is caused by the sintering of the Ni particles with an apparent activation energy of 161 kJ mol −1 . 13 In order to overcome catalyst deactivation due to sintering, overcoating the catalyst with a metal oxide layer by atomic layer deposition (ALD) has been shown to be an effective catalyst stabilization strategy.…”
Section: Introductionmentioning
confidence: 99%
“…The main reaction equation is: CH 4 + CO 2 = 2CO + 2H 2 , ∆H 298K = 247 kJ/mol because of the high stability of methane and carbon dioxide molecules. Studies have shown that DRM has the following advantages: (1) Wide sources of raw materials are utilized to turn waste into treasure, thereby reducing atmospheric pollution; (2) compared to wet reforming and partial oxidation reforming of methane, DRM can save nearly half of methane; (3) the ratio of H 2 to CO is close to 1, appropriate for oxo reaction (hydroformylation reaction in the presence of Co or Rh where olefins reacts with CO and H 2 to produce aldehydes) and FTS reaction (also known as Fischer-Tropsch Synthesis, a process where CO and H 2 react to form olefins and other valuable products); (4) the reaction has a large reaction heat, which can be used as energy storage and medium transmission, such as solar energy storage [1,[8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, the existing industrialized processes of hydrogen production include the reforming of natural gas, partial oxidation of oil and steam gasification of coal. 17–52 Among them, the reforming of fossil fuels has drawn attention due to the mature technology and abundant sources of raw materials, where methane is converted to hydrogen and carbon monoxide. 53–63 In some applications such as fuel cells, it is impossible to use a gas mixture of carbon monoxide and hydrogen due to the poisoning effect of carbon monoxide on catalysts and platinum electrodes, resulting in deactivation.…”
Section: Introductionmentioning
confidence: 99%